2004 Proceedings. 54th Electronic Components and Technology Conference (IEEE Cat. No.04CH37546)
DOI: 10.1109/ectc.2004.1320339
|View full text |Cite
|
Sign up to set email alerts
|

A multiple frequency signal generator for 802.11a/b/g VoWLAN type applications using organic packaging technology

Abstract: This paper proposes a signal generator that simultaneously generates multiple frequencies while using the same set of passive components. The first example demonstrates the capability of simultaneously generating 2.45GHz and 5.2 GHz (WLAN aiblg). Additionally, an oscillator capable of concurrently generating 900 MHz and 1.9 GHz (GSM and DCS-1800 hand) is also presented. This paper uses the theory of multi-resonant passives and shows their immediate effects on different topologies of signal generators that gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In [14], a single-layer LCP shows excellent material characteristics up to 110 GHz. The single-layer LCP substrate for RF front ends has been characterized and applied to various applications such as low-noise amplifiers (LNAs), filters, baluns, and voltage-controlled oscillators (VCOs) [15]. Even though performances of RF front-end components are directly related to the quality factor (Q) of passives, this does not imply that every passive should have a high Q.…”
mentioning
confidence: 99%
“…In [14], a single-layer LCP shows excellent material characteristics up to 110 GHz. The single-layer LCP substrate for RF front ends has been characterized and applied to various applications such as low-noise amplifiers (LNAs), filters, baluns, and voltage-controlled oscillators (VCOs) [15]. Even though performances of RF front-end components are directly related to the quality factor (Q) of passives, this does not imply that every passive should have a high Q.…”
mentioning
confidence: 99%
“…Although, this paper discusses work done primarily on passives on LCP based substrates, the authors have shown the application of this technology to realize other components such as single and multiband oscillators [12,20], low-noise amplifiers (LNAs) [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, integration of high performance passives such as filters, in organic substrates or the PCB can eliminate the total dependence on LTCC and would help reduce module surface area, save costs and increase reliability. The work done in [6][7][8][9][10][11][12][13][14][15][16] illustrates organic process technologies, similar to PCB technology, that are being targeted as a cost-effective alternative to the primary technologies of choice namely ceramic based devices mentioned earlier. The work done in [6,[9][10][11]14,16] illustrates example of filters implemented using lumped element and transmission line topologies to realize components at 2.4GHz, SGHz, 1.9GHz and frequencies > 5GHz.…”
Section: Multilayer Ceramic (Mlc) [4]mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the resonant property of lumped capacitors C1 and C2, which resonate with parasitic inductances LC1 and LC2 respectively, could also do this. For simplicity the only parasitic [7,8,12,and 131 by the authors were used as the guidelines for the design of stand alone components. Inductors in the range of 1nH-lOnH [7,8] can be embedded in stripline, CPW, microstrip or a combination of the above with Qs in the range of 30-200 based on the topology and configuration used.…”
Section: Design Of Filtersmentioning
confidence: 99%